Hyperechogenic renal parenchyma in potential live related kidney donors: Does it justify exclusion? - Fouda, AM; Sobh, MA; Moustafa, F; Sally, S; Bakr, MA; Refaei, A; EI-Mekresh, MM; Azab, ME; Ghoneim, MA (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">The aim of this work is to asses theimportance of ultrasonic grade I echogenicity inpotential kidney donors in the absence of urinaryabnormality and with perfect renal function.Thirty four living related kidney donors with thisabnormality were included, age range between 23-48years. Ten matched healthy donors were studied ascontrols. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">All cases were thoroughly investigated includingmeasuring GFR by isotopic scan and estimation ofrenal reserve by dopamine and aminoacid infusion.Renal biopsy was done for 17 cases of theechogenicity group and 8 controls. Our resultsshowed that the renal reserve was comparable in bothgroups. Glomerular changes were found in 41% ofapparently normal donors and only one case ofcontrols. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Grade I echogenicity may be sign ofunrecognised kidney disease. Renal biopsy ismandatory when such related donors are the onlyavailable.